Optical laminate and display device using the same

JP7936829B2Active Publication Date: 2026-10-16TOPPAN TOMOEGAWA OPTICAL FILM CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024036314
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2026-10-16
Estimated Expiration
2044-03-08

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、二軸延伸ポリエチレンテレフタレートフィルムを基材として用い、折り曲げ耐性を有し、かつ、ニジムラが抑制された光学積層体及びこれを用いた画像表示装置を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936829000009
    Figure 0007936829000009
  • Figure 0007936829000010
    Figure 0007936829000010
  • Figure 0007936829000001
    Figure 0007936829000001
Patent Text Reader

Abstract

To provide an optical laminate which uses biaxially stretched polyethylene terephthalate film as a base material and offers bending resistance and suppressed rainbow mura, and to provide an image display device using the same.SOLUTION: An optical laminate for use in image display devices is provided, the optical laminate comprising a light-transmissive substrate consisting of a biaxially stretched polyethylene terephthalate film and having in-plane birefringence, and an optical functional layer provided on one surface of the light-transmissive substrate, the optical functional layer having a total haze of 5% or greater. The light-transmissive substrate has an in-plane retardation Re, defined by a formula (1): Re=(nx-ny)×d, of 2,000 nm to 7,500 nm, inclusive, where nx represents a refractive index in a slow axis direction, ny represents a refractive index in a fast axis direction, and d represents a thickness of the light-transmissive substrate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical laminate provided on the front side of an image display panel and a display device using the same.

Background Art

[0002] Conventionally, as the base material of the optical film disposed on the surface of an image display device, a triacetyl cellulose (TAC) film that has no in-plane retardation and is excellent in visibility has been used. However, the TAC film has a problem that it causes warpage of the image display device by absorbing moisture in the air. Therefore, polyethylene terephthalate (PET) films with low moisture absorption have attracted attention, and in recent years, ultra-high retardation (ultra-high Re) PET films are sometimes used (for example, see Patent Documents 1 and 2).

[0003] When an image display device is viewed through a polarizing plate such as polarized sunglasses, the vibration plane of light emitted from the image display device and the transmission axis of the polarizing plate such as polarized sunglasses are orthogonal to each other, so that a so-called blackout phenomenon occurs in which the image display device is viewed as dark. As a technique for solving this blackout, for example, Patent Document 3 describes that the angle formed by the slow axis of the optical laminate and the absorption axis of the polarizer used in the liquid crystal display device is set to 45°±15°.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Patent Document 3

Summary of Invention

Problems to be Solved by the Invention

[0005] When using ultra-high RePET film as a substrate, blackout during polarized sunglasses use can be suppressed by adjusting the angle of the slow axis, but because it is a uniaxially oriented film, it has the problem of poor bending resistance. On the other hand, biaxially oriented PET film has significantly improved bending resistance and can suppress blackout regardless of the angle of the slow axis, but it has the problem of noticeable streaks due to in-plane phase difference.

[0006] Therefore, the present invention aims to provide an optical laminate and an image display device using the same, which use a biaxially oriented polyethylene terephthalate film as a base material, have bending resistance, and suppress variegation. [Means for solving the problem]

[0007] The optical laminate according to the present invention comprises a biaxially oriented polyethylene terephthalate film, a light-transmitting substrate having birefringence in its plane, and an optical functional layer provided on one side of the light-transmitting substrate. The optical functional layer is either an anti-glare layer or a layer in which an anti-glare layer and a low refractive index layer are laminated in that order from the light-transmitting substrate side, and the internal haze of the optical laminate is 2% to 31.5%. The total haze of the optical stack is 8.7% or more. The average inclination angle θa of the surface irregularities present on the optical functional layer is 0.39° or more and 4.58° or less, the maximum height Rz of the surface irregularities present on the optical functional layer is 0.280 μm or more and 2.982 μm or less, and the in-plane retardation Re of the light-transmitting substrate, as defined by the following formula (1), is 2,272 nm or more and 7,500 nm or less. Re = (nx - ny) × d (1) Here, nx: Refractive index in the slow phase axis direction ny: Refractive index in the phase-advancing axis direction d: Thickness of the light-transmitting substrate That is the case.

[0008] The image display device according to the present invention comprises an image display panel and the optical laminate described above. [Effects of the Invention]

[0009] According to the present invention, it is possible to provide an optical laminate and an image display device using the same, which use a biaxially oriented polyethylene terephthalate film as a base material, have bending resistance, and suppress variegation. [Brief explanation of the drawing]

[0010] [Figure 1] A schematic cross-sectional view showing an example of an optical laminate according to the embodiment. [Figure 2] A schematic cross-sectional view showing another example of the optical laminate according to the embodiment. [Modes for carrying out the invention]

[0011] Figure 1 is a schematic cross-sectional view showing an example of an optical laminate according to the embodiment.

[0012] The optical laminate 10 comprises a light-transmitting substrate 1 and an anti-glare layer (AG layer) 2 laminated on one side of the light-transmitting substrate 1. The optical laminate 10 is an optical film (also called an "AG film") that suppresses reflection of external light by scattering incident light with the fine irregularities on the surface of the anti-glare layer 2 and the particles inside. In the optical laminate 10 shown in Figure 1, the anti-glare layer 2 corresponds to the optical functional layer.

[0013] Figure 2 is a schematic cross-sectional view showing another example of the optical film according to the embodiment.

[0014] The optical laminate 20 comprises a light-transmitting substrate 1, an anti-glare layer 2 laminated on one side of the light-transmitting substrate 1, and a low refractive index layer (LR layer) 3 laminated on the surface of the anti-glare layer 2, with a refractive index lower than that of the anti-glare layer 2. The optical laminate 20 is an optical film that suppresses reflection and glare of ambient light by utilizing the scattering and optical interference of incident light caused by fine irregularities on the outermost surface and internal particles (also referred to as an "AGLR film"). In the optical laminate 20 shown in Figure 2, the anti-glare layer 2 and the low refractive index layer 3 correspond to the optical functional layers.

[0015] The details of each layer are explained below.

[0016] The light-transmissive substrate is a transparent film that serves as the base of the optical laminate. As the light-transmissive substrate, a biaxially stretched polyethylene terephthalate film having birefringence is used, which has an in-plane retardation Re defined by the following formula (1) of 2,000 nm or more and 7,500 nm or less. Re=(nx-ny)×d (1) Herein, nx: the refractive index in the slow axis direction (direction with a larger refractive index) of the light-transmissive substrate ny: the refractive index in the fast axis direction of the light-transmissive substrate d: the thickness of the light-transmissive substrate is defined as above.

[0017] When the in-plane retardation Re of the light-transmissive substrate is less than 2,000 nm, the thickness of the light-transmissive substrate becomes small, which may lead to deteriorated handleability or insufficient surface hardness when the optical laminate is constituted, and thus this case is not preferred. When the in-plane retardation Re of the light-transmissive substrate exceeds 7,500 nm, the thickness of the light-transmissive substrate becomes large, which may increase raw material costs or raise the total thickness when the optical laminate is constituted, and thus this case is not preferred.

[0018] It is preferable to use, as the light-transmissive substrate, one that satisfies the following condition (2). (nx-ny)<0.06 (2)

[0019] When the value of nx-ny is 0.06 or more, the resistance to tearing and breaking, which are mechanical properties, is lowered due to excessive stretching, and thus this case is not preferred.

[0020] Further, it is preferable to use, as the light-transmissive substrate, one having a thickness direction retardation Rth' of the light-transmissive substrate represented by the following formula (3) of 9,500 nm or more and 18,000 nm or less. Rth'=(nx-nz)×d (3) Herein, nz: the refractive index in the thickness direction is defined as above.

[0021] If the retardation Rth' in the thickness direction of the light-transmitting substrate is less than 9,500 nm, the thickness of the light-transmitting substrate becomes thin, which may result in insufficient mechanical strength when forming an optical laminate, and this is undesirable. Conversely, if the retardation Rth' in the thickness direction of the light-transmitting substrate exceeds 18,000 nm, the thickness of the light-transmitting substrate becomes large, which is undesirable as it hinders the thinning of the optical laminate.

[0022] Furthermore, it is preferable to use a light-transmitting substrate in which the ratio Nz' represented by the following formula (4) is 1.5 or more and 5.5 or less. Nz'=Rth' / Re (4)

[0023] When the ratio Nz' is within the above range, the birefringence and thickness of the light-transmitting substrate are within an appropriate range, making it possible to achieve both mechanical strength and suppression of unevenness when constructing an optical laminate.

[0024] The thickness of the light-transmitting substrate 1 is not particularly limited, but is preferably 35 to 200 μm, and more preferably 35 to 125 μm. The surface of the light-transmitting substrate 1 may be subjected to a surface modification treatment to improve adhesion with other layers to be laminated. Examples of surface modification treatments include alkali treatment, corona treatment, plasma treatment, sputtering, coating of surfactants or silane coupling agents, and Si deposition.

[0025] The anti-glare layer 2 is a functional layer that forms the fine uneven surface of the optical laminate 10.

[0026] The anti-glare layer 2 is formed by applying a coating solution containing an active energy ray-curable compound and organic and / or inorganic fine particles (fillers) to a light-transmitting substrate 1 and curing the coating film.

[0027] As active energy ray curable compounds, for example, monofunctional, bifunctional, or trifunctional or more (meth)acrylate monomers can be used. In this specification, "(meth)acrylate" is a general term for both acrylate and methacrylate, and "(meth)acryloyl" is a general term for both acryloyl and methacryloyl.

[0028] Examples of monofunctional (meth)acrylate compounds include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfluryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth)acrylate. Phosphate, Isodecyl (meth)acrylate, Lauryl (meth)acrylate, Tridecyl (meth)acrylate, Cetyl (meth)acrylate, Stearyl (meth)acrylate, Benzyl (meth)acrylate, 2-Ethoxyethyl (meth)acrylate, 3-Methoxybutyl (meth)acrylate, Ethyl carbitol (meth)acrylate, Phosphate (meth)acrylate, Ethylene oxide-modified Phosphate (meth)acrylate, Phenoxy (meth)acrylate, Ethylene oxide-modified Phenoxy (meth)acrylate, Propylene oxide Phenoxy(meth)acrylate modified with ethylene oxide, nonylphenol(meth)acrylate, ethylene oxide-modified nonylphenol(meth)acrylate, propylene oxide-modified nonylphenol(meth)acrylate, methoxydiethylene glycol(meth)acrylate, methoxypolyethylene glycol(meth)acrylate, methoxypropylene glycol(meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, 2-(meth) ) Acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hexahydrohydrogen phthalate, 2-(meth)acryloyloxypropyl tetrahydrohydrogen phthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, 2-adamantane,Examples include adamantane derivative mono(meth)acrylates such as adamantyl acrylate, which has a monovalent mono(meth)acrylate derived from adamantanediol.

[0029] Examples of difunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, and other di(meth)acrylates.

[0030] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tris-2-hydroxyethyl isocyanurate tri(meth)acrylate, glycerin tri(meth)acrylate, and other trifunctional (meth)acrylate compounds such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and ditrimethylolpropane tri(meth)acrylate. Examples include polyfunctional (meth)acrylate compounds with three or more functions, such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate, as well as polyfunctional (meth)acrylate compounds in which some of these (meth)acrylates are substituted with alkyl groups or ε-caprolactone.

[0031] Furthermore, urethane (meth)acrylates can also be used as polyfunctional monomers. Examples of urethane (meth)acrylates include those obtained by reacting a product obtained by reacting a polyester polyol with an isocyanate monomer or prepolymer with a hydroxyl group (meth)acrylate monomer.

[0032] Examples of urethane (meth)acrylates include pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer.

[0033] The polyfunctional monomers described above may be used individually or in combination of two or more. Furthermore, the polyfunctional monomers described above may be monomers in the coating solution or oligomers in which a portion has been polymerized.

[0034] Organic fine particles are materials that primarily form fine irregularities on the surface of the anti-glare layer 2, thereby imparting the function of diffusing ambient light. As organic fine particles, resin particles made from light-transmitting resin materials such as acrylic resin, polystyrene resin, styrene-(meth)acrylic acid ester copolymer, polyethylene resin, epoxy resin, silicone resin, polyvinylidene fluoride, and polyfluoroethylene resins can be used. To adjust the refractive index and dispersion of the resin particles, two or more types of resin particles with different materials (refractive index) may be mixed and used. The average particle size of the organic fine particles is preferably 0.5 to 10 μm.

[0035] The inorganic fine particles added to the anti-glare layer forming composition are preferably nanoparticles with an average particle size of 10 to 200 nm.

[0036] Inorganic microparticles are primarily used to regulate the sedimentation and aggregation of organic microparticles in the anti-glare layer 2. Examples of inorganic microparticles include silica microparticles, metal oxide microparticles, and various mineral microparticles. Examples of silica microparticles include colloidal silica and silica microparticles surface-modified with reactive functional groups such as (meth)acryloyl groups. Examples of metal oxide microparticles include alumina, zinc oxide, tin oxide, antimony oxide, indium oxide, titania, and zirconia. Examples of mineral microparticles include mica, synthetic mica, vermiculite, montmorillonite, iron montmorillonite, bentonite, bydelite, saponite, hectorite, stevensite, nontronite, magadiite, islarite, kanemite, layered titanate, smectite, and synthetic smectite. Mineral microparticles may be natural products or synthetic products (including substituted and derivative products), and mixtures of both may be used. Among mineral microparticles, layered organic clay is more preferred. Layered organic clay refers to a material in which organic onium ions are introduced between layers of swellable clay. The organic onium ions are not limited as long as they can be organicated by utilizing the cation exchange properties of the swellable clay. When layered organic clay minerals are used as mineral fine particles, the synthetic smectite described above can be suitably used. Synthetic smectite has the function of increasing the viscosity of the anti-glare layer forming composition, suppressing the sedimentation of resin particles and inorganic fine particles, and adjusting the surface irregularities of the optical functional layer.

[0037] A polymerization initiator may be added to cure the anti-glare layer formation composition by ultraviolet irradiation. A polymerization initiator that generates radicals upon ultraviolet irradiation can be used. Examples of polymerization initiators include radical polymerization initiators such as acetophenone-based, benzophenone-based, thioxanthone-based, benzoin, benzoin methyl ether, and acylphosphine oxide. Examples of polymerization initiators include diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-diethoxyacetophenone, 1-hydroxycyclohexylphenyl ketone, 2,2-dimethoxyphenylacetophenone, dibenzoyl, benzoin, benzoin methyl ether, benzoin ethyl ether, p-chlorobenzophenone, p-methoxybenzophenone, Michler ketone, acetophenone, and 2-chlorothioxanthone. One of these may be used alone, or two or more may be used in combination.

[0038] Furthermore, the composition for forming the anti-glare layer may contain antifouling agents, leveling agents, oil repellents, water repellents, and anti-fingerprint agents as components to improve antifouling properties. Fluorine-containing compounds and silicone compounds can be suitably used as these additives. In addition, various additives such as antistatic agents, defoaming agents, antioxidants, ultraviolet absorbers, infrared absorbers, colorants, light stabilizers, polymerization inhibitors, and photosensitizers may be added as needed.

[0039] Furthermore, a solvent may be added to the anti-glare layer-forming composition as needed. As a solvent, one or more of the following can be used in combination: alcohols such as methanol, ethanol, 1-propanol, 2-propanol, butanol, isopropyl alcohol, isobutanol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone; ketone alcohols such as diacetone alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, diethyl carbitol, and propylene glycol monomethyl ether; esters such as methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, and amyl acetate; ethers such as dimethyl ether and diethyl ether; N-methylpyrrolidone, dimethylformamide, etc.

[0040] The low refractive index layer 3 has a refractive index lower than that of the lower anti-glare layer 2 and is a functional layer that suppresses reflection through optical interference.

[0041] The low refractive index layer 3 can be formed by applying a composition containing an active energy ray curable compound to the surface of the anti-glare layer 2 and curing the coating film. The low refractive index layer 3 may also contain low refractive index fine particles for refractive index adjustment.

[0042] Suitable low-refractive-index nanoparticles include, for example, nanoparticles of LiF, MgF, 3NaF·AlF or AlF (all with a refractive index of 1.4), or Na3AlF6 (cryllite, refractive index 1.33), or silica nanoparticles with internal voids. Silica nanoparticles with internal voids are advantageous for lowering the refractive index of the low-refractive-index layer 3 because the void portion can have the refractive index of air (approximately 1). Specifically, porous silica particles and silica particles with a shell structure can be used. However, low-refractive-index nanoparticles are not always necessary; if the refractive index of the active energy ray curable compound after curing is lower than the refractive index of the anti-glare layer 2, the low-refractive-index nanoparticles may be omitted.

[0043] As the active energy ray curable compound, the polymerizable compound described in the section on the anti-glare layer can be used. In addition, the polymerization initiator and solvent described above may be added to the composition for forming the low refractive index layer as appropriate.

[0044] The composition for forming a low refractive index layer may contain antifouling agents, leveling agents, oil repellents, water repellents, and anti-fingerprint agents as components to improve antifouling properties. Fluorine-containing compounds and silicone compounds can be suitably used as these additives. In addition, various additives such as antistatic agents, defoaming agents, antioxidants, ultraviolet absorbers, infrared absorbers, colorants, light stabilizers, polymerization inhibitors, and photosensitizers may be added as needed.

[0045] One or more other functional layers, such as a hard coat layer, a high refractive index layer, a medium refractive index layer, an antistatic layer, an electromagnetic wave shielding layer, an infrared absorbing layer, an ultraviolet absorbing layer, or a color correction layer, may be laminated between the light-transmitting substrate 1 and the anti-glare layer 2.

[0046] The coating method for the above-mentioned anti-glare layer forming composition and low refractive index layer forming composition is not particularly limited, and can be applied using, for example, a spin coater, roll coater, reverse roll coater, gravure coater, microgravure coater, knife coater, bar coater, wire bar coater, die coater, dip coater, spray coater, applicator, etc.

[0047] Here, we will describe in detail the surface irregularities of the optical laminate according to this embodiment.

[0048] The total haze of the optical laminate according to the present invention is preferably 5% or more. When the total haze is 5% or more, ambient light is sufficiently diffused and streaks originating from the light-transmitting substrate can be suppressed. A total haze of 22.0 to 71.6% is more preferable. When the total haze is within this more preferable range, it is advantageous for suppressing streaks.

[0049] The surface haze of the optical laminate according to the present invention is preferably 3% or more. When the surface haze is 3% or more, ambient light is sufficiently diffused and variegation originating from the light-transmitting substrate can be suppressed. The surface haze is more preferably 12.0 to 68.6%. When the surface haze is within the more preferable range, it is advantageous for suppressing variegation.

[0050] The internal haze of the optical laminate according to the present invention is preferably 2% or more. When the internal haze is 2% or more, ambient light is sufficiently diffused, and streaks originating from the light-transmitting substrate can be suppressed. The internal haze is more preferably 3.1 to 55.6%. When the internal haze is within the more preferable range, it is advantageous for suppressing streaks.

[0051] The above-mentioned total haze, surface haze, and internal haze values ​​were measured in accordance with JIS K7136.

[0052] In the optical laminate according to the present invention, it is preferable that the value of Δn × total haze is 0.2 or more (where Δn = nx - ny). A value of Δn × total haze of 0.2 or more is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, within the above range, it is more preferable that the value of Δn × total haze is 0.39 to 2.55, and even more preferable that the value of Δn × total haze is 0.78 to 2.55.

[0053] In the optical laminate according to the present invention, it is preferable that the Re × total haze value is 10,000 or more. When the Re × total haze value is 10,000 or more, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, within the above range, it is more preferable that the Re × total haze value is 19,725 to 301,028, and even more preferable that the Re × total haze value is 58,679 to 301,028.

[0054] Furthermore, in the optical laminate according to the present invention, it is preferable that the value of Δn × surface haze is 0.12 or greater. When the value of Δn × surface haze is 0.12 or greater, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, within the above range, it is more preferable that the value of Δn × surface haze is 0.15 to 2.44, and even more preferable that the value of Δn × surface haze is 0.37 to 2.44.

[0055] Furthermore, in the optical laminate according to the present invention, it is preferable that the Re× surface haze value is 6,000 or more. When the Re× surface haze value is 6,000 or more, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, within the above range, it is more preferable that the Re× surface haze value is 9,544 to 182,972, and even more preferable that the Re× surface haze value is 32,007 to 182,972.

[0056] Furthermore, in the optical laminate according to the present invention, it is preferable that the value of Δn × internal haze is 0.08 or greater. When the value of Δn × internal haze is 0.08 or greater, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, it is more preferable that the value of Δn × internal haze is 0.11 to 1.98 within the above range.

[0057] Furthermore, in the optical laminate according to the present invention, it is preferable that the Re×internal haze value is 4,000 or more. When the Re×internal haze value is 4,000 or more, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, it is more preferable that the Re×internal haze value is between 8,268 and 207,991 within the above range.

[0058] In the optical laminate according to the present invention, it is preferable that the arithmetic mean roughness Ra of the surface of the optical functional layer is 0.04 μm or more, and the average inclination angle θa of the irregularities present on the surface of the optical functional layer is 0.30° or more. When the arithmetic mean roughness Ra and average inclination angle θa are within the above range, ambient light can be sufficiently diffused and unevenness originating from the light-transmitting substrate can be suppressed. From the viewpoint of suppressing unevenness in the optical laminate, within the above range, the arithmetic mean roughness Ra is 0.070~ 0.536 The particle size is preferably μm, and the average tilt angle θa is preferably 0.39 to 4.58°.

[0059] Furthermore, in the optical laminate according to the present invention, it is preferable that the maximum height Rz of the irregularities present on the surface of the optical functional layer is 0.2 μm or more. When the maximum height Rz is 0.2 μm or more, ambient light can be sufficiently diffused and irregularities originating from the light-transmitting substrate can be suppressed. From the viewpoint of suppressing irregularities in the optical laminate, it is more preferable that the maximum height Rz is 0.280 to 2.982 μm within the above range.

[0060] Furthermore, in the optical laminate according to the present invention, it is preferable that the Ra×Rsm value is 1.6 or greater. Here, Rsm is the average length of the contour curve elements. When the Ra×Rsm value is 1.6 or greater, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, within the above range, it is more preferable that the Ra×Rsm value is 1.77 to 23.09.

[0061] Furthermore, in the optical laminate according to the present invention, it is preferable that the value of Ra×θa is 0.018 or higher. When the value of Ra×θa is 0.018 or higher, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, it is more preferable that the value of Ra×θa is 0.027 to 2.457 within the above range.

[0062] Furthermore, in the optical laminate according to the present invention, it is preferable that the value of Ra×Rsm×θa is 1.6 or greater. When the value of Ra×Rsm×θa is 1.6 or greater, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, within the above range, the value of Ra×Rsm×θa is 1.79. ~ A value of 105.78 is more preferable.

[0063] Furthermore, in the optical laminate according to the present invention, it is preferable that the value of Δn×Ra is 0.002 to 0.02. When the value of Δn×Ra is 0.002 to 0.02, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, it is more preferable that the value of Δn×Ra is 0.0025 to 0.0191 within the above range.

[0064] Furthermore, in the optical laminate according to the present invention, it is preferable that the Re×Ra value is 140 to 1,500. When the Re×Ra value is 140 to 1,500, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, it is more preferable that the Re×Ra value is 159 to 1,431 within the above range.

[0065] Furthermore, in the optical laminate according to the present invention, it is preferable that the value of Δn×θa is 0.01 to 0.17. When the value of Δn×θa is 0.01 to 0.17, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, it is more preferable that the value of Δn×θa is 0.014 to 0.163 within the above range.

[0066] Furthermore, in the optical laminate according to the present invention, it is preferable that the value of Re×θa is 800 to 12,500. When the value of Re×θa is 800 to 12,500, it is advantageous in terms of suppressing unevenness in the optical laminate. From the viewpoint of suppressing unevenness in the optical laminate, it is more preferable that the value of Re×θa is 886 to 12,218 within the above range.

[0067] The optical laminate according to this embodiment can be used to construct an image display device by laminating it to the outermost surface of an image display panel such as a liquid crystal panel or an organic EL panel. A touch panel may be provided between the optical laminate and the image display panel. Because the optical laminate according to this embodiment uses a biaxially oriented PET film as the light-transmitting substrate, it has excellent moisture resistance and bending resistance, and the light diffusion properties of the anti-glare layer suppress the unevenness originating from the biaxially oriented PET film, making it suitable as an optical film to be provided on the outermost surface of an image display device. Since the optical laminate has bending resistance, it can also be used as an optical film for a foldable image display device.

[0068] As described above, the optical laminate according to this embodiment is equipped with a biaxially oriented PET film having an in-plane retardation Re of 2,000 to 7,500 nm as a light-transmitting substrate. When using a biaxially oriented PET film, there is a problem in that the unevenness is noticeable, but it is possible to suppress the occurrence of unevenness by controlling the optical properties (anti-glare and anti-reflective properties) of the entire optical laminate with an optical functional layer. When using a biaxially oriented PET film with an in-plane retardation Re of less than 2,000 nm, the surface hardness tends to decrease as the thickness of the light-transmitting substrate becomes thinner, but in this embodiment, by using a biaxially oriented PET film with an in-plane retardation Re of 2,000 to 7,500 nm, it is possible to secure the surface hardness required for the optical laminate. Furthermore, when using a PET film called an ultra-high RePET film as a light-transmitting substrate, blackout when using polarized sunglasses can be eliminated by adjusting the angle of the slow axis of the light-transmitting substrate, but since the ultra-high RePET film is a uniaxially oriented film, it has the problem of being weak in bending resistance. In this embodiment, since the light-transmitting substrate is a biaxially oriented PET film, it has good bending resistance, and even when intended for use in applications where it is viewed through a polarizing plate such as polarized sunglasses, it has the advantage of eliminating blackout without considering the angle of the slow axis of the light-transmitting substrate. In other words, the optical laminate according to this embodiment simultaneously solves the problems that occur when using a PET film with low in-plane retardation Re (less than 2,000 nm) and the problems that occur when using a PET film with high in-plane retardation Re (greater than 7,500 nm), making it suitable for use in image display devices that are viewed through a polarizing plate such as polarized sunglasses. [Examples]

[0069] The following describes specific examples of how the present invention is implemented.

[0070] First, we will explain the method for manufacturing a light-transmitting substrate.

[0071] <Unstretched film> Polyethylene terephthalate raw material was melted at 285°C and filtered through a stainless steel sintered filter (nominal filtration accuracy: 95% cut of 10μm particles). The resulting mixture was laminated in a 2-type, 3-layer confluence block, extruded into a sheet from a die, and then cooled and solidified using an electrostatic casting method on a casting drum with a surface temperature of 30°C to obtain an unstretched film. During this process, the discharge rate of each extruder was adjusted so that the thickness ratio of the three layers was 10:80:10. Next, the unstretched PET film was coated on both sides using the reverse roll method, with a dry coating amount of 0.08 g / m². 2 To achieve this, the adhesive modification coating solution was applied and then dried at 80°C for 20 seconds.

[0072] <Uniaxially oriented film> The unstretched film with the coated layer was guided into a tenter stretcher, and while holding the ends of the film with clips, it was guided into a hot air zone at a temperature of 125°C and stretched to 4.0 times its original width. Next, while maintaining the stretched width, it was processed at a temperature of 225°C for 30 seconds, and then a 3% relaxation treatment was performed in the width direction to obtain a uniaxially oriented PET film with a film thickness of 80 μm.

[0073] <Biaxially oriented film> The unstretched film with the coated layer formed on it was heated to 105°C using a heated roll group and an infrared heater, and then stretched by 2.6 times in the running direction and 4.0 times in the width direction using a roll group with a difference in peripheral speed to obtain biaxially oriented PET films with thicknesses of 38, 50, 75, 125, and 188 μm. In addition, a biaxially oriented PET film with a thickness of 23 μm was obtained by stretching it by 1.4 times in the running direction and 4.0 times in the width direction.

[0074] Tables 1-4 below show the compositions of the anti-glare layer forming coating liquid and the low refractive index layer forming coating liquid used in the examples and comparative examples. Each coating liquid was diluted to a concentration suitable for coating using the solvents listed in Tables 1-4. The addition ratios of each component shown in Tables 1-4 represent the proportion (mass%) of the total solid content mass of the coating liquid. Here, the total solid content of the coating liquid for forming the optical functional layer refers to the components excluding the solvent. Therefore, the blending ratio (mass%) of resin particles and inorganic fine particles in the total solid content of the coating liquid for forming the optical functional layer is equal to the content (mass%) of resin particles and inorganic fine particles in the optical functional layer, which is the cured film of the coating liquid for forming the optical functional layer. In Table 1, "-" indicates that the corresponding material was not blended.

[0075] [Table 1]

[0076] [Table 2]

[0077] [Table 3]

[0078] [Table 4]

[0079] The materials used in Tables 1-4 are as follows:

[0080] <Coating liquid for forming an anti-glare layer (hard coat layer)> ·UV / EB curable resin Light Acrylate PE-3A (Pentaerythritol Triacrylate), manufactured by Kyoeisha Chemical Co., Ltd. • Photopolymerization initiator Omnirad® 184 (1-hydroxycyclohexyl phenyl ketone), IGM Resins BV • Resin particles (organic spherical fillers) (1) Acrylic-styrene copolymer, average particle size 3.5 μm, n=1.515 (2) Acrylic-styrene copolymer, average particle size 3.5 μm, n=1.565 (3) Acrylic-styrene copolymer, average particle size 3.5 μm, n=1.555 (4) Polystyrene, average particle size 3.5 μm, n=1.595 (5) Acrylic-styrene copolymer, average particle size 2.0 μm, n=1.595 • Shapeless silica particles Average particle size 2.7 μm, n=1.45, Fuji Silicia Co., Ltd. • Leveling agent F565, DIC Corporation • Nanoparticles (organosilica sol) MEK-ST-40, Nissan Chemical Corporation

[0081] <Coating liquid for forming a low refractive index layer> Binder resin Light Acrylate PE-3A (Pentaerythritol Triacrylate), Kyoeisha Chemical Co., Ltd. • Photopolymerization initiator Omnirad® 184 (1-hydroxycyclohexyl phenyl ketone), IGM Resins BV • Hollow silica (porous silica fine particle dispersion) (1) Average particle diameter 60nm (2) Average particle diameter 75nm • Leveling agent RS-75, DIC Corporation

[0082] (Examples 1, 2, 7, 8, 11, Comparative Example 3) A coating solution for forming an anti-glare layer having the composition described in Tables 1 to 4 was prepared and applied to a biaxially oriented PET film as shown in Table 5. After drying the coating film, the coating film was polymerized and cured by irradiation with ultraviolet light to form an anti-glare layer. Next, a coating solution for forming a low refractive index layer having the composition described in Tables 1 to 4 was prepared and applied to the anti-glare layer. After drying the coating film, the coating film was polymerized and cured by irradiation with ultraviolet light to form a low refractive index layer. Through these steps, an optical laminate (AGLR film) was obtained.

[0083] (Examples 3-6, 9, 10, 12-16, Comparative Examples 4, 5) An optical laminate (AG film) was obtained in the same manner as in Example 1, except that a low refractive index layer was not formed on the anti-glare layer.

[0084] (Comparative Example 1) A hard coat layer forming solution having the composition shown in Table 4 was prepared and applied to the uniaxially oriented PET film shown in Table 5 so that the cured film thickness would be 5 μm. After drying the coating film, the coating film was polymerized and cured by irradiation with ultraviolet light to form a hard coat layer. An optical laminate (HC film) was obtained through the above process.

[0085] (Comparative Example 2) An optical laminate (HC film) was obtained in the same manner as in Comparative Example 1, except that the biaxially oriented PET film described in Table 5 was used as the light-transmitting substrate.

[0086] (Hayes) The haze value was measured using a haze meter (NDH4000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7136. Here, the haze value of the optical laminate was defined as the total haze. In addition, the internal haze of the optical laminate was defined as the haze value of the optical laminate minus the haze value of the adhesive-backed transparent sheet, which was measured by laminating an adhesive-backed transparent sheet to the surface of the optical functional layer of the optical laminate. For the adhesive-backed transparent sheet, a polyethylene terephthalate film (thickness 38 μm) coated with an acrylic adhesive (thickness 10 μm) was used. Surface haze was calculated using the following formula. Surface haze (%) = Total haze (%) - Internal haze (%)

[0087] (Retardation) The in-plane phase difference and thickness-direction phase difference of the fabricated uniaxially or biaxially oriented PET films were measured using a phase difference film / optical material inspection device (RETS-100, manufactured by Otsuka Electronics Co., Ltd.). The measurement conditions were as follows: [Measurement conditions] • Retardation measurement method: Rotational analyzer method • Measurement spot diameter: φ5mm • Inclination angle range: 0°、40° • Measurement wavelength range: 400nm to 800nm The value is calculated using the formula N=(nx+ny+nz) / 3, based on the average refractive index N: nx, ny, and nz of the light-transmitting substrate. In the case of PET film, N=1.660 Note that the in-plane retardation Re and the thickness-direction retardation Rth' are values ​​at a wavelength of 589 nm.

[0088] [Surface shape analysis] The surface irregularities of the optical functional layer of the optical laminates in each example and comparative example were measured using an optical interference method with a non-contact surface and layer cross-sectional shape measurement system (measurement device: BartScan R3300FL-Lite-AC, analysis software: VS-Viewer6, manufactured by Ryoka Systems Co., Ltd.). The measurement data was analyzed using the device's particle analysis software to determine the arithmetic mean roughness Ra, maximum height Rz, average length Rsm of the curved elements, and average inclination angle θa of the low refractive index layer surface.

[0089] Furthermore, the average surface irregularities are generated by the analysis conditions in the cross-sectional profile (multiline) of VS-Viewer. The arithmetic mean roughness Ra, maximum height Rz, average length Rsm of the curved elements, and average slope angle θa obtained from the cross-sectional profile obtained by averaging the cross-sectional profiles of the 6 set measurement cursor points are defined as the arithmetic mean roughness Ra, maximum height Rz, average length Rsm of the curved elements, and average slope angle θa of the surface irregularities in this invention.

[0090] Measurements were performed using the device's measurement software under the following conditions, and an image file representing the measurement results of surface irregularities was obtained. ·Optical conditions Camera: Sony HR-50 1 / 3 inch Objective lens: 10XDI (10x magnification) Image lens (lens barrel): 0.5x Zoom lens: 1x Light source / wavelength filter: 520nm ND filter: Not used A-Stop (Opening Restriction): Not used (fully open) F-Stop (Field of View Aperture): Not used (fully open) • Measurement conditions Measurement device: Piezo Measurement mode: Phase Scan speed: 4 μm / sec Scan range: -10 to 10 μm Effective pixels: 50% Measurement area: 704.192μm×938.923μm

[0091] The acquired image files were analyzed using the device's analysis software under the following conditions. ·Analysis conditions (VS-Viewer6) Surface correction: 4th order S filter: Automatic L filter: Not used ·Particle analysis conditions (VS-Viewer6) Analysis type: sudden analysis Image correction: None Height threshold: 0.1 μm Particle shaping: None

[0092] (Methods for calculating Ra, Rz, Rsm, and θa) In the acquired images after applying surface correction (4th order) and an S filter, the measurement cursors were set at 200 μm, 500 μm, and 800 μm in the vertical direction (X direction) and at 200 μm, 400 μm, and 600 μm in the horizontal direction (Y direction). The values ​​of Ra, Rz, Rsm, and θa were obtained for each cursor position (a total of 6 locations: 3 in the cross section parallel to the X direction and 3 in the cross section parallel to the Y direction), which are automatically calculated by the VS-Viewer's cross section profile, and the average value (arithmetic mean) of the obtained values ​​was used as the measurement result.

[0093] (Nijimura's evaluation) Observations of Nijimura under the assumption of using polarized sunglasses were conducted as follows: Backlight (brightness 5,000 cd / m²) 2 An observation sample was prepared by arranging a first polarizer, an optical laminate of the example or comparative example, and a second polarizer (assuming polarized sunglasses) in that order on a display with a certain degree of brightness. At this time, the absorption axis of the first polarizer was orthogonal to the vertical direction of the display, and the absorption axis of the second polarizer was orthogonal to the absorption axis of the first polarizer. In addition, the orientation in which the vertical direction of the display and the slow phase axis of the light-transmitting substrate of the optical laminate are parallel was set as the reference rotation position (0°), and the optical laminate was rotated clockwise by 45°, and then another 45° (a rotation position 90° from the reference rotation position), and the nucleation was observed visually at each orientation. The observer made observations from a position directly in front of the display, 50-60 cm away from the display, and from an oblique position 50-60 cm away from the display, tilted 45° left and right with respect to the normal direction when viewed from the front. The nucleation was evaluated based on the observation results according to the following criteria. -: The screen blacks out, making it impossible to determine Nijimura's status (unusable). ×: Nijimura occurs, making it unusable. △: Some streaks may occur, but they do not pose a practical problem. ○: A slight blemish may occur, but it does not pose a practical problem. ◎: No occurrence of Nijimura (outstandingly good)

[0094] (bending resistance) A tabletop durability testing machine (manufactured by Yuasa System Equipment Co., Ltd.) was fitted with a planar material unloaded U-shaped stretch test fixture (DMX-FS), and each sample was attached to it so that it was flat. The optical functional layer was placed on the outside, and the bending operation was performed continuously so that the distance between opposing surfaces was 2 mm. After performing the bending operation 50,000 times and 200,000 times, the presence or absence of fracture at the bend was visually checked and evaluated according to the following criteria. ○: No breakage occurred at the flexed portion in any of the continuous folding tests. ×: In any of the continuous folding tests, a fracture occurred at the bending point.

[0095] (Pencil hardness) Pencil hardness was evaluated in accordance with JIS K5400-1900. The pencil hardness of the protective layer surface was measured using pencils (uni, Mitsubishi Pencil Co., Ltd.) and a Clemens scratch tester (HA-301, Tester Industry Co., Ltd.). The test was repeated while varying the pencil hardness, and the change in appearance due to scratches was observed visually. The highest hardness at which no scratches were observed was used as the evaluation value. A pencil hardness of H or higher was considered acceptable.

[0096] Table 5 shows the type, thickness, and optical properties such as retardation of the light-transmitting substrate for each example and comparative example, along with the layer structure of the optical laminate.

[0097] [Table 5]

[0098] Table 6 shows the measured values ​​for the surface roughness of the optical laminates for each example and comparative example.

[0099] [Table 6]

[0100] Table 7 shows the measured values ​​for the haze of the optical laminates for each example and comparative example.

[0101] [Table 7]

[0102] Table 8 shows the evaluation results for unevenness, bending resistance, and pencil hardness of the optical laminates for each example and comparative example.

[0103] [Table 8] All optical laminates in Examples 1 to 16 used a biaxially oriented PET film with an in-plane retardation Re of 2,000 to 7,500 nm as the light-transmitting substrate. Therefore, even when considering the use of polarized sunglasses, blackout did not occur regardless of the slow axis direction of the light-transmitting substrate, and variegation was suppressed by the optical functional layer. Furthermore, because all optical laminates in Examples 1 to 16 used a biaxially oriented PET film, they exhibited good surface hardness and bending resistance.

[0104] In contrast, the optical laminate according to Comparative Example 1 uses a uniaxially oriented PET film with high in-plane retardation Re as the light-transmitting substrate. Therefore, blackout occurs depending on the slow axis direction of the light-transmitting substrate, making it unsuitable for applications where polarized sunglasses are intended.

[0105] Furthermore, neither of the optical laminates in Comparative Examples 2 and 3 could suppress the unevenness, and were therefore unsuitable for applications involving the use of polarized sunglasses.

[0106] The optical laminate in Comparative Example 4 used a biaxially oriented PET film with an in-plane retardation Re of less than 2,000 nm, so while the unevenness was suppressed, the pencil hardness was insufficient. [Industrial applicability]

[0107] This invention can be used as an optical laminate provided on the front side of an image display panel. [Explanation of symbols]

[0108] 1. Light-transmitting substrate 2 Anti-glare layer 3 Low refractive index layer 10, 20 optical laminates

Claims

1. An optical laminate used in an image display device, A light-transmitting substrate consisting of a biaxially oriented polyethylene terephthalate film having birefringence in its plane, The light-transmitting substrate comprises an optical functional layer provided on one side thereof, The optical functional layer is either an anti-glare layer, or a layer in which an anti-glare layer and a low refractive index layer are laminated in order from the light-transmitting substrate side. The internal haze of the optical laminate is 2% or more and 31.5% or less. The total haze of the optical laminate is 8.7% or more. The average inclination angle θa of the irregularities present on the surface of the optical functional layer is 0.39° or more and 4.58° or less. The maximum height Rz of the irregularities present on the surface of the optical functional layer is 0.280 μm or more and 2.982 μm or less. An optical laminate in which the in-plane retardation Re of the light-transmitting substrate, as defined by the following formula (1), is 2,272 nm or more and 7,500 nm or less. Re=(nx-ny)×d (1) Here, nx: Refractive index in the slow phase axis direction ny: Refractive index in the phase-advancing axis direction d: Thickness of the light-transmitting substrate That is the case.

2. The optical laminate according to claim 1, wherein the surface haze is 3% or more.

3. The optical laminate according to claim 1, satisfying the following condition (2). (nx-ny)<0.06 (2)

4. The optical laminate according to claim 1, wherein the retardation Rth' in the thickness direction of the light-transmitting substrate, represented by the following formula (3), is 9,500 nm or more and 18,000 nm or less. Rth'=(nx-nz)×d (3) Here, nz: Refractive index in the thickness direction That is the case.

5. The optical laminate according to claim 1, wherein the ratio Nz' represented by the following formula (4) is 1.5 or more and 5.5 or less. Nz'=Rth' / Re (4)

6. The optical laminate according to claim 1, wherein no breakage occurs when a folding test is repeated 200,000 times in which the optical functional layer is placed on the outside and the laminate is folded 180° such that the distance between opposing surfaces is 2 mm.

7. Image display panel, An image display device comprising an optical laminate according to any one of claims 1 to 6 provided on the front surface of the image display panel.

Citation Information

Patent Citations

  • Spareetyre retaining apparatus

    JP1978004939A

  • Roll rearranging device of rolling mill

    JP1985044118A

  • High heat conductive substrate

    JP1987056385A

  • Polarizer protective film, and polarizer and liquid crystal display using the same

    JP2008003541A

  • Antiglare film, polarizing plate, and image display device

    JP2014016602A